Observation of a new superfluid phase for 3He embedded in nematically ordered aerogel - N. Zhelev (Nature Portfolio, 2016)
Anisotropic disorder is predicted to change the stability of the superfluid state in3He and leads to new phases. Here, Zhelev et al. report signatures of the phase transitions in 3He confined in an extremely anisotropic ordered aerogel including a new polar phase.